Simulation of cold-powder snow avalanches considering daily snowpack and weather situations - J. Glaus; J. Glaus; K. Wikstrom Jones; P. Bartelt; P. Bartelt; M. Christen; M. Christen; L. Stoffel; J. Gaume; J. Gaume; J. Gaume; Y. Bühler; et al. (Natural Hazards and Earth System Sciences)
Snow avalanches are rapid gravitational mass movements that pose a significant hazard to both humans and infrastructure, including traffic lines. Risk management in mountainous regions usually relies on the experience of avalanche experts, observations in the field, weather and snowpack measurements, and numerical simulations.